Effect of computerized cognitive rehabilitation in comparison between young and old age after traumatic brain injury. Issue 33 (19th August 2022) - Kim, Seong-Hun; Gwak, Dae-Won; Jeong, Jae-Gyeong; Jung, Hyunwoo; Min, Yu-Sun; Kim, Ae-Ryoung; Jung, Tae-Du
Abstract : Introduction: Cognitive dysfunction reduces patients' quality of life and social participation with traumatic brain injury (TBI). Computerized cognitive rehabilitation is increasingly being used for cognitive therapy in TBI patients. The purpose of this study was to investigate the influence of age on the effect of computerized cognitive rehabilitation in cognitive dysfunction after TBI. Material and methods: A total of 34 patients with cognitive dysfunction after TBI were enrolled. Participants performed 30 sessions of computerized cognitive rehabilitation (Comcog) for 6 weeks. A cognitive evaluation was performed before and after treatment with Mini-Mental State Examination (MMSE) and Computerized Neurophyschologic Test (CNT). Results: There were no cognitive tests that differed between the young group and the old group at baseline. However, after computerized cognitive rehabilitation, the young group showed significant improvement compared to the old group in verbal memory, visual memory, attention, and visuo-motor coordination tests. The young group showed improvement in MMSE, verbal and visual memory, and visuo-motor coordination tests after computerized cognitive rehabilitation. In contrast, the old group showed significant improvement only in MMSE and visual learning test, one of the visual memory tests. Conclusion: Our findings demonstrate that age may be an important factor related to the effect of computer cognitive rehabilitation on cognitive dysfunction after TBI. Methodologically more ordered studies with larger sample sizes are needed in the future.